2007
DOI: 10.1007/s10815-007-9129-6
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase (MMP)-2 and MMP-9 in seminal plasma

Abstract: Purpose To evaluate the latent and active forms of MMP-2 and MMP-9 in human semen samples and to investigate their association with semen parameters. Methods Basic semen analysis was performed in 82 semen samples. Seminal plasma was analyzed with gelatin zymography. Results Both latent and active forms of MMP-2 and MMP-9 were detected in human seminal plasma. The latent forms were the predominant ones. MMP-2 and MMP-9, either in latent or active forms, were not correlated with semen parameters. ProMMP-9 levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 13 publications
(19 reference statements)
3
30
0
2
Order By: Relevance
“…Based on previous reports (Metayer et al 2002;Shimokawa et al 2002;McCauley et al 2001;Tentes et al 2007), the bands with 225, 78 and 66 kDa correspond to dimer-MMP-9, proMMP-2 and active MMP-2. The variation in molecular weights (by 10 to 15 kDa) of gelatinases of different origins can be result of different glycosylation (Metayer et al 2002).…”
Section: +mentioning
confidence: 60%
See 2 more Smart Citations
“…Based on previous reports (Metayer et al 2002;Shimokawa et al 2002;McCauley et al 2001;Tentes et al 2007), the bands with 225, 78 and 66 kDa correspond to dimer-MMP-9, proMMP-2 and active MMP-2. The variation in molecular weights (by 10 to 15 kDa) of gelatinases of different origins can be result of different glycosylation (Metayer et al 2002).…”
Section: +mentioning
confidence: 60%
“…Similarly, in human seminal plasma a higher concentration of pro-MMP-9 was detected in semen with abnormally low sperm concentration (Tentes et al 2007). The same study reported that inactive or active forms of MMP-2 and MMP-9 do not correlate with semen indicators.…”
Section: +mentioning
confidence: 95%
See 1 more Smart Citation
“…Matrix metalloproteinases and their tissue inhibitors play a key role in many physiological processes, including ovulation, fertilization and implantation (Hulboy et al, 1997). Metalloproteases like MMP-2, MMP-9 and serine proteinases have been detected in turkey and human seminal plasma (Kotlowska et al, 2005) and their latent forms in canine seminal plasma and deteriorated semen samples with unsatisfactory quality traits (Tentes et al, 2007). The inactive forms were inversely correlated with semen quality and active forms were positively correlated with semen quality traits and sperm functionality (Saengsoi et al, 2011).…”
Section: Proteases and Proteases Inhibitors Of Seminal Plasmamentioning
confidence: 99%
“…So far, only the existence of two MMPs, namely MMP-2 and MMP-9, has been reported in human seminal plasma (Baumgart et al, 2002;Buchman-Shaked et al, 2002;Shimokawa Ki et al, 2002;Tentes et al, 2007). However, correlation of these results with semen parameters led to contradictory findings.…”
Section: Introductionmentioning
confidence: 99%